A comprehensive review on applications of 3D printing in natural fibers polymer composites for biomedical applications. (1st September 2022) - Chohan, Jasgurpreet Singh; Kumar, Raman; Singh, Sandeep; Sharma, Shubham; Ilyas, R A
Abstract: Over the past few decades, three-dimensional (3D) printing technologies have surpassed the conventional manufacturing techniques due to their wide applications and advantages. The applications of 3D printing in biomedical field is ever increasing due to improvement in accuracy and surface quality of products. The development of biomedical implants through patient specific data and rapid tooling techniques has revolutionized the research activities. Now-a-days, the metal printers have capability to directly create metal implants using biocompatible metallic alloys. This paper focuses on the potential applications of 3D printing in biomedical fields with specific emphasis on tissue engineering and bio-printing of organs using bio-inks. This paper also reviews various biocompatible and biodegradable materials used in recent in-vivo and in-vitro studies. It has been deduced from the study that use of natural fibers in polymers resulted in improved mechanical strength of products. Also, the implementation of additive manufacturing technologies for production of composites would lead to production of customized product.